Infection Leading to Breast Abscess Formation in Pregnancy: A Case Report - Yu J; Chen J; Huang T; Gu X (International Medical Case Reports Journal)
Jiangting Yu,1 Jiaying Chen,1 Tianjian Huang,1 Xidong Gu2 1Department of Breast Surgery, The First School of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou, Zhejiang Province, People’s Republic of China; 2Department of Breast Surgery, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Xidong Gu, Department of Breast Surgery, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, Zhejiang, People’s Republic of China, Email 20083011@zcmu.edu.cnIntroduction: Breast abscess, the most severe complication of mastitis, occurs when an infection spreads through the nipple into the breast tissue, contaminating the milk ducts and forming a purulent cavity. Nonetheless, this condition is less common in pregnant women. Staphylococcus aureus is the predominant causative agent in lactating women; however, Prevotella bivia-associated breast abscesses during pregnancy remain clinically rare, with limited documented cases.Case Presentation: A 26-year-old Chinese woman with G1P0 singleton at 33 weeks of pregnancy presented with right breast pain and lumps without obvious triggers, accompanied by enlarged right axillary lymph nodes and a large amount of pus with a peculiar odor in the right breast. After breast ultrasonography, cytological puncture smear, pus culture, and metagenomic next-generation sequencing, the patient was confirmed to have gestational mastitis with P. bivia infection. Given that the patient had a high-risk pregnancy, the use of antibiotics sensitive to Prevotella, such as metronidazole, might affect the intrauterine fetus, and infection with this bacterium could increase the risk of placental abruption and intrauterine fetal distress. Based on the obstetrician’s and pediatrician’s recommendations, the patient opted for a cesarean section at 37 weeks to facilitate the delivery of a healthy neonate weighing 3110 g (Apgar scores of 10 at 1 min and 5 min) in the left anterior sacral position and was advised to opt for lactation-suppressing medication and postpartum antibiotics.Conclusion: This case highlights the importance of close monitoring of pus characteristics (eg, color, odor, and volume) in pregnancy-associated breast abscesses to expedite the diagnosis of infectious mastitis and pathogen identification. Treatment with small incision drainage and targeted antibiotics during pregnancy significantly improved the outcomes. Postpartum breast milk return and combined antibiotic therapy further contributed to the resolution of inflammation.Keywords: Prevotella bivia, mastitis in pregnancy, anaerobic infection, high-risk pregnancy status